Enlarged PML-nuclear bodies trigger conflicting cell cycle signal-mediated cytotoxicity in leukemia cells - Tomohisa Baba; Soichiro Kumamoto; Yuta Moriguchi; Soji Morishita; Atsushi Hirao; Yoshikazu Johmura (Cell Death and Disease)
Abstract Accumulating evidence suggests that mitogenic signaling during cell cycle arrest can lead to severe cytotoxic outcomes, such as senescence, though the underlying mechanisms remain poorly understood. Here, we explored the link between cell cycle dynamics and the formation of PML-nuclear bodies (PML-NBs), intranuclear structures known to mediate cellular stress responses. Our findings demonstrate that PML-NBs increase their number during interphase arrest. Moreover, the activation of mitogenic ERK signaling by all-trans retinoic acid (ATRA) during CDK4/6 inhibitor-induced cell cycle arrest synergistically enhances the formation of larger PML-NBs by associating with SUMO. This enlargement, triggered by the simultaneous engagement of opposing cell cycle signals, leads to potent cytotoxicity accompanied by either terminal differentiation or apoptosis, depending on the cell type, across multiple acute myeloid leukemia (AML) cell lines. Importantly, in an AML mouse model, this combination treatment significantly improved therapeutic efficacy with minimal effects on normal hematopoiesis. Our results introduce conflicting cell cycle signal-induced cytotoxicity as a promising therapeutic strategy for AML.